Respuestas

2014-01-31T06:23:14+01:00
(6x²-4x) / (2x) = 2x(3x-2) / 2x    .................factor comun en el numerador
                    = 3x-2                .................simplifico 2x con 2x

(7ax²-3by²)² = (7ax²)² - (2)(7ax²)(3by²) + (3by²)².......resuelvo el binomio al cuadrado
                  = 49a²x^4 -14abx²y² + 9b²y^4.......resuelvo el binomio al cuadrado

(ax+3by)²= (ax)² + (2)(ax)(3by) + (3by)²......resuelvo el binomio al cuadrado
             = a²x² + 6abxy + 9b²y².....resuelvo el binomio al cuadrado

:)